PENGARUH PENGGUNAAN MEDIA INTERNET TERHADAP HASIL BELAJAR SISWA KELAS XI IIS SMAN 2 PONTIANAK - Wahyudi, Jarot; Asriati, Nuraini; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis purpose of this reasearh is to know the influence of internet media toward students outcome of class XI IIS on economic subjects on SMAN 2 Pontianak. The methods used in this research was descrptive method in the form of a relation study. The population of this research were 158 students totalled, samples taken using the random sampling technique or random sample of 113 students. Data collection using question form, and documentation. The results showed that (1) the use of internet media on economic subject in clss XI IIS on SMAN 2 Pontianak indicated that 57.5% of respondents were good. (2) the results of a study on the economics subject in class XI IIS on SMAN 2 Pontianak showed that 56.6% of respondents were excellent. (3) there is the influence of the usage of internet media toward students outcome of class XI IIS on economics subject in SMAN 2 pontianak with a valueÂ t calculate>t table (26,831>1,981) as well as the value of 0,005<0,000 signifcance, then Ha accapted and H0 rejected. (4) the magnitude of the influence of the usage of internet media towars the students outcome of class XI IIS on economic subject in SMAN 2 Pontianak were 86.6%.Keyword: Learning Media, Internet Media, The Results Of The Study